Analysis of the Effect of Motivation and Job Training on the Performance of Production Unit Employees at PT. Kayu Permata Bekasi - Dewi Rahayu; Dede Otto Tirtadinata; Reni Yesi (Mulia Pratama, 2023)
This research is motivated by a decrease in employee performance at PT. Jewel Wood. This decrease in performance indicates a decrease in production quality, this occurs because the company in terms of motivating employees and providing job training is not optimal, among other things that need to be optimized, namely the provision of salaries according to company standards or UMK, provision of health facilities, provision of transportation and periodization length of service extended in accordance with the criteria for lengthening of service period. The work environment can affect employee performance, the results of the targets (measures) that have been agreed upon by the company, both in terms of quantity and quality of the responsibilities that have been given. Employee performance will usually increase if the aspects of motivation and job training are fulfilled and are optimal in achieving goals. Good performance produces quality products, therefore special training is needed that can increase employee competence according to expertise in the field of production. Employee performance will also decrease if the Company does not pay attention to employee welfare, such as the several aspects above that affect employee performance. This research uses quantitative methods. Data collected by questionnaire technique. Respondents in this study were 50 people. Three hypotheses are formulated and tested using Regression Analysis. The results showed that motivation and job training had a significant relationship with employee performance. The results of the research as attached and processed using the SPSS Motivation and Job Training turned out to have a positive and significant effect on employee performance at PT. Kayu Permata can be seen through SPSS (Statistical Product and Service Solution) version 26, that the R² (R. Square) value is 70.2%. Suggestions that can be used by management in determining company or organizational policies in the future regarding motivation, job training and employee performance, namely increasing salary aspects according to employee expectations, providing training in accordance with the areas required by the company and optimizing employee welfare to support performance quality.